Evaluating Training Methods for Future Technical Specialists - Cherkashyn, Andrii; Asieieva, Iryna; Koshkarov, Yurii; Melnyk, Tamara; Panfilov, Yurii (Journal of Technical Education and Training, 2024)
This study evaluates the efficacy of current training methods for technical specialists in higher education, focusing on the development of professional competencies, skills, and personal qualities. Utilizing a mixed-methods approach, including questionnaires and interviews among students of National Technical University “Kharkiv Polytechnic Institute” and National University of Civil Protection of Ukraine, the research identifies gaps in traditional educational frameworks and the challenges posed by distance learning. Key findings reveal a significant satisfaction with the quality of professional training among students, underscored by the effective use of modern teaching methods and technologies. However, difficulties with distance learning and technology utilization were notable concerns. The study recommends the creation of online laboratories, development of training programs for modern technologies, incorporation of joint student projects, and enhanced collaboration between universities and industry to improve training quality. These recommendations aim to align technical education more closely with industry demands and technological advancements. The implications for Technical and Vocational Education and Training (TVET) suggest a paradigm shift towards integrating interactive, technology-driven methods into curricula, addressing the digital divide, and fostering industry-academia partnerships. This approach promises to prepare a workforce adept at navigating the complexities of modern and future job markets, emphasizing the practical application of theoretical knowledge and the importance of continuous learning and adaptability.